Liberation of three dihydrogens from two ethene molecules as mediated by the tantalum nitride anion cluster Ta3N2− at room temperature. Issue 4 (13th January 2017) - Hu, Ji-Chuang; Xu, Lin-Lin; Li, Hai-Fang; Valdivielso, David Yubero; Fielicke, André; He, Sheng-Gui; Ma, Jia-Bi
Abstract : The full dehydrogenation of C2 H4 by gas-phase anions Ta3 N2 − as well as the structure and reactivity of the M–N–C cluster is reported for the first time. Abstract : The reactivity of gas-phase cluster anions Ta3 N2 − with C2 H4 under thermal collision conditions was studied by mass spectrometry in conjunction with density functional theory calculations. The full dehydrogenation of the C2 H4 molecule was observed, with the formation of two dihydrogen molecules. Interestingly, the two carbon atoms originating from the first C2 H4 molecule are used to construct another cluster Ta3 N2 C2 −, which can activate one more C2 H4 releasing one H2 molecule. Therefore, three dihydrogen molecules are liberated from two ethene molecules in the overall reaction. The full dehydrogenation of C2 H4 by gas-phase anions as well as the structure and reactivity of M–N–C (M: transition metal) cluster is reported for the first time. The properties of Ta3 N2 − and Ta3 N2 C2 − elucidated herein are of use in providing fundamental information that is necessary to tailor the design of new and effective catalysts by applying the related materials.